Advances in improving tolerance to waterlogging in Brachiaria grasses - Cardoso Arango, Juan Andrés; Jiménez, Juan; Rincón, Joisse D.; Guevara, Edward D.; Hoek, Rein van der; Jarvis, Andy; Peters, Michael; Miles, John W.; Ayarza, Miguel Angel; Cajas, Socorro; Rincón, Álvaro; Mateus, Henry; et al. (New South Wales Department of Primary Industry, 2013)
Poor drainage is found on about 11.3% of agricultural land in Latin America where physiography promotes flooding, high groundwater tables, or stagnant surface water (waterlogging). Waterlogging drastically reduces oxygen diffusion into the soil causing hypoxia which is the main limitation that reduces root aerobic respiration and the absorption of minerals and water. Under waterlogging conditions plants can adapt with traits and mechanisms that improve root aeration such as production of aerenchyma and development of adventitious roots. During the rainy season Brachiaria pastures are exposed to waterlogging conditions that can severely limit pasture productivity and hence animal production. The main objective of an inter-institutional and multidisciplinary project was to identify Brachiaria hybrids combining waterlogging tolerance with high forage yield and quality to improve meat and milk production and mitigate the impacts of climate change in the humid areas of Latin America. Researchers at the Centro Internacional de Agricultura Tropical (CIAT) have developed a screening method to evaluate waterlogging tolerance in Brachiaria. Using this method, 71 promising hybrids derived from three Brachiaria species (B. ruziziensis, B. brizantha, and B. decumbens) were evaluated. Four hybrids were identified as superior in waterlogging tolerance. Their superiority was based on greater green leaf biomass production, a greater proportion of green leaf to total leaf biomass, greater green leaf area, leaf chlorophyll content, and photosynthetic efficiency, and reduced dead leaf biomass. These hybrids together with previously selected hybrids and germplasm accessions are being field-tested for waterlogging tolerance in collaboration with National Agricultural Research Institutions and farmers from Colombia, Nicaragua, and Panama.